Central Banking and the Crisis. A Comparison of the Federal Reserve and the European Central Bank Measures, and the ECB’s Changing Role in the EU Economic Governance System (2016)
The European Central Bank (ECB) has received a lot of criticism for its too little, too late performance to ease market pressures during the economic crisis. At the same time, the ECB and the Federal Reserve (FED) have managed the new economic realities that have emerged in the international context differently. Despite the criticisms, the European Central Bank is the European Union institution that has assumed more control due to the new model of economic governance of the EU. Why did the Federal Reserve act so nimbly and quickly to calm the markets, while the ECB was so cautious in managing monetary policy? The aim of this paper is to perform a comparative analysis of the management of interest rates and other monetary policy measures undertaken by the Central Bank and the Federal Reserve during the economic crisis, as well as to understand the changes in the context of the ECB and the emergence of its authority within the European Union’s economic governance model since 2011. Thus, in order to carry out a scrupulous exposition, we will also limit the time frame of this study to the 2007-2014 period.